Renewable Ruse: Bioenergy Development in North Carolina’s Coastal Plains - Dana Powell; Jefferson Currie; Danielle Koonce; Mac Legerton; Rebecca Witter (Engaging Science, Technology, and Society, 2024)
Rural communities in eastern North Carolina are responding to the emergence of bioenergy development as an extension of environmental injustices, rather than sustainable solutions to climate change as presented by state and industry actors. We examine how biomass and biogas development entrench logics of extraction, rather than transition, as they are built as extensions of pre-existing concentrated animal feeding operations (CAFOs) in a landscape prone to climatic fluctuations. Using a polyvocal approach to knowledge co-production that builds from multi-year collaborative ethnography, the co-authored text demonstrates a commitment to the value of environmental justice (EJ) leaders’ knowledge—to advance environmental analytics. We argue that despite its claims, bioenergy operates as a ruse of renewable energy: it is a technological sleight of hand, that deepens rather than mitigates exposure to socio-ecological harm. Discursively hinged to sustainability claims, biomass and biogas attempt to signify a temporal, moral, and technological breakaway toward a different kind of techno-social future when, in fact, there is no real rupture from the well-established export-driven, extractivist logics of production.